R E V I E W: Citanduy river diversion, advantages and disadvantages plan to conserve mangrove ecosystem in Segara Anakan - KUSUMO WINARNO; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2003)
Mangrove ecosystem at Segara Anakan lagoon, Cilacap having specific characteristics so that in developing this areashould consider the conservation aspect. This area is the widest conserved-mangrove ecosystem at Java, and the placefor breeding of many species of fish, crustacean and others. Thousand families of fisheries were supported both direct andindirectly from this ecosystem. However, along with the development activities in the watershed of Citanduy,Cimeneng/Cikonde and other rivers connected to the area has brought about the increase of sediment, and threaten theexistence of the lagoon and surrounding mangrove ecosystem. Diversion of Citanduy river, dredging sediment, and reboisation of the watershed river was a preference of conserving the ecosystem, however, the diversion could be forming a new ecosystem, that actually threat the fisheries and tourism activities at Pangandaran, Ciamis.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: mangrove, Citanduy river, Segara Anakan lagoon, sedimentation, diversion